2002
DOI: 10.2307/3583253
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Measuring HIV Prevalence: The Case of Nigeria

Abstract: This article reviews methodologies and data sources that have been used to measure HIV prevalence and sexual behaviours associated with the transmission of HIV in Nigeria. The review includes 35 studies on HIV prevalence and methodology and 34 studies on sexual behaviour published between 1990 and 2000. As at 1999, 5.1-5.4% of http://www.bioline.org.br/request?rh02031 (1 of 24)10/20/2004 11:17:27 AM http://www.bioline.org.br/request?rh02031 the general population was estimated to be infected with HIV. Trend da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…It could be because when sex is unprotected, or a new condom is not properly used each time, the risk of HBsAg increases. Data on sexual behaviours indicated that risky behaviours are very common in Nigeria; while condom use remains low due to religious and cultural beliefs (Pauchaud et al, 2002). In couples, insistence on use of condom during sex may be a sign of lack of trust towards the partner, which may generate acrimony (Otori et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It could be because when sex is unprotected, or a new condom is not properly used each time, the risk of HBsAg increases. Data on sexual behaviours indicated that risky behaviours are very common in Nigeria; while condom use remains low due to religious and cultural beliefs (Pauchaud et al, 2002). In couples, insistence on use of condom during sex may be a sign of lack of trust towards the partner, which may generate acrimony (Otori et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Data on sexual behaviors indicate that risky behaviors are very common in Nigeria, while condom use remains low. [23] In couples, insistence on use of condom during sex may be a sign of lack of trust towards the partner, which may generate acrimony. Unprotected sexual intercourse is the major route of human procreation among couples; and unfaithfulness on the part of any of the partners by way of being involved in unprotected extramarital relationship constitutes a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The Nigerian government's current projections are that between 6 and 10 percent of the adult population aged 15-45 will be infected by 2010 and that between 8.1 and 9.4 million people will have died from AIDS-related causes by 2015 (National Action Committee on AIDS 2003). Although the numbers and the trajectory of Nigeria's epidemic are difficult to predict, few experts would dispute that, given the current trends and Nigeria's massive pop-ulation, in the next ten to 15 years Nigeria will have the largest number of people living with HIV/AIDS of any country in Africa (Panchaud et al 2002).…”
Section: Aids In Nigeriamentioning
confidence: 99%